Numerical Analysis of a TCR Adaptive to Different Tree Diameters for Unstructured Forest Environment: A TCR of Variable Diameter with Different Tree Diameters. (16th February 2023) - Wu, Zhe; Wang, Xigui; Zhang, Zhiqin
Abstract : This paper proposes the optimal design and simulation analysis of a robot for tree-climbing, which has the ability to climb up the tree trunk to adapt to different tree diameter changes. In an unstructured forest environment, considering that the Tree-Climbing Robot (TCR) may collide with branches, reducing the success rate of tree climbing, the mechanical structure and movement strategy to avoid branches are predesigned. The presented TCR mimics several design principles that have been adapted to arboreal animals, including claw-hand grasping and climbing gait movements, and is optimally designed to achieve high manoeuvrability on irregularly shaped trees. Based on the D - H parameterization method, the kinematics model of the TCR is developed and its kinematic equations are solved. The accuracy of the kinematic equations is verified by MATLAB, and the reachable area of the working space of the manipulator of the TCR is determined. Using ADAMS to analyse the kinematics and dynamics of the climbing process of the TCR, the rationality of the gait planning of the robot is verified, and the time-varying characteristic curves of each physical quantity of each structural joint are derived and further simulated through numerical analysis, the results of which will profoundly validate the technical feasibility and design innovation of this presented TCR.